Biochemical Characterization of the Fusarium graminearum Candidate ACC-Deaminases and Virulence Testing of Knockout Mutant Strains - Svoboda, Thomas; Parich, Alexandra; Güldener, Ulrich; Schöfbeck, Denise; Twaruschek, Krisztian; Václavíková, Marta; Hellinger, Roland; Wiesenberger, Gerlinde; Schuhmacher, Rainer; Adam, Gerhard (Frontiers in Plant Science, 2019)
Fusarium graminearum is a plant pathogenic fungus which is able to infect wheat and other economically important cereal crop species. The role of ethylene in the interaction with host plants is unclear and controversial. We have analyzed the inventory of genes with a putative function in ethylene production or degradation of the ethylene precursor ACC. F. graminearum, in contrast to other species, does not contain a candidate gene encoding ethylene-forming enzyme. Three genes with similarity to ACC synthases exist; heterologous expression of these did not reveal enzymatic activity. The F. graminearum genome contains in addition two ACC deaminase candidate genes. We have expressed both genes in E. coli and characterized the enzymatic properties of the affinity-purified products. One of the proteins had indeed ACC deaminase activity, with kinetic properties similar to ethylene-stress reducing enzymes of plant growth promoting bacteria. The other candidate was inactive with ACC but turned out to be a D-cysteine desulfhydrase. Since it had been reported that ethylene insensitivity in transgenic wheat increased Fusarium resistance and reduced the content of the mycotoxin deoxynivalenol in infected wheat, we generated single and double knockout mutants of both genes in the F. graminearum strain PH-1. No statistically significant effect of the gene disruptions on fungal spread or mycotoxin content was detected, indicating that the ability of the fungus to manipulate the production of the gaseous plant hormones ethylene and H2S is dispensable for full virulence.